2020
DOI: 10.1021/acs.cgd.9b01394
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Growth of 6H-SiC and 3C-SiC in an Al–Si–C System at 820 °C: Effect of the Reaction Path on the SiC Polytype

Abstract: Many of the properties of SiC are decided by the polytype. In the present work, the effect of the reaction path on the SiC polytype is studied. Two kinds of SiC particles were prepared at 820 °C in an Al–Si–C system. Results show that 6H-SiC with a hexagonal structure and 3C-SiC with a face-centered cubic structure were obtained separately with a liquid–solid reaction and master alloy method. Further research revealed that 6H-SiC was formed via a one-step reaction with graphite as the precursor, while 3C-SiC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…23 As shown in Fig. 4 and the perfect 3C-SiC crystal was the combination of rhombic dodecahedron and cube simple forms, 24 the morphology of the 3C-SiC particles was more diverse. In Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…23 As shown in Fig. 4 and the perfect 3C-SiC crystal was the combination of rhombic dodecahedron and cube simple forms, 24 the morphology of the 3C-SiC particles was more diverse. In Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This indicated that the synthesized p-type SiC powder was mainly composed of 3C-SiC and a small portion of 6H-SiC. Due to the fact that the perfect 6H-SiC crystal possessed a hexagonal conical prism shape from the side view and a regular hexagon shape from the top view and the perfect 3C-SiC crystal was the combination of rhombic dodecahedron and cube simple forms, 24 the morphology of the 3C-SiC particles was more diverse. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polytypes, occurring in different structural modifications, are a special case of polymorphs, which share identical close-packed planes but differ only in the stacking sequence in the third dimension normal to these planes. Polytypes commonly exist in group II–VI, III–V, and IV-IV compound semiconductors, whose structures generally display cubic zinc-blende (ZB) and hexagonal wurtzite (WZ) forms. As one of the typical II–VI semiconductors, cadmium selenide (CdSe) has attracted extensive interest over the past 20 years, owing to its robust synthetic method and its ability to tune the optical behavior across the entire visible spectrum.…”
Section: Introductionmentioning
confidence: 99%